(untitled) (Kronika Bydgoska, 2018)
Units of the Blue Regiment for the Defense of the Country comprising civilians were established in several cities of Pomerania and Kuyavia, including Bydgoszcz, on the initiative of Gen. Józef Haller on August 6, 1939. Their armament and activities were approved by Gen. Michał Tokarzewski, commander of DOK VIII. After the outbreak of World War II, these formations initiated activities directed against Polish citizens of German nationality, which resulted in about 1,300 victims. In addition, it led to civilian defense against the Wehrmacht entering such towns as Bydgoszcz, Inowrocław, Nakło, Mogilno, and Trzemeszno. After their victorious end of this campaign, the Germans retaliated against the Polish population, murdering about 30,000 people, primarily members of the intelligentsia.